Objective measurement of vocalizations in the assessment of autism spectrum disorder symptoms in preschool age children. Issue 9 (25th April 2022) - Moffitt, Jacquelyn M.; Ahn, Yeojin Amy; Custode, Stephanie; Tao, Yudong; Mathew, Emilin; Parlade, Meaghan; Hale, Melissa; Durocher, Jennifer; Alessandri, Michael; Perry, Lynn K.; Messinger, Daniel S.
Abstract: Assessment of autism spectrum disorder (ASD) relies on expert clinician observation and judgment, but objective measurement tools have the potential to provide additional information on ASD symptom severity. Diagnostic evaluations for ASD typically include the autism diagnostic observation schedule (ADOS‐2), a semi‐structured assessment composed of a series of social presses. The current study examined associations between concurrent objective features of child vocalizations during the ADOS‐2 and examiner‐rated autism symptom severity. The sample included 66 children (49 male; M  = 40 months, SD = 10.58) evaluated in a university‐based clinic, 61 of whom received an ASD diagnosis. Research reliable administration of the ADOS‐2 provided social affect (SA) and restricted and repetitive behavior (RRB) calibrated severity scores (CSS). Audio was recorded from examiner‐worn eyeglasses during the ADOS‐2 and child and adult speech were differentiated with LENA SP Hub. PRAAT was used to ascertain acoustic features of the audio signal, specifically the mean fundamental vocal frequency (F0) of LENA‐identified child speech‐like vocalizations (those with phonemic content), child cry vocalizations, and adult speech. Sphinx‐4 was employed to estimate child and adult phonological features indexed by the average consonant and vowel count per vocalization. More than a quarter of the variance in ADOS‐2 RRB CSS was predicted by the combination of child phoneme count per vocalization and child vocalization F0. Findings indicate that both acoustic and phonological features of child vocalizations are associated with expert clinician ratings of autism symptom severity. Lay Summary: Determination of the severity of autism spectrum disorder is based in part on expert (but subjective) clinician observations during the ADOS‐2. Two characteristics of child vocalizations—a smaller number of speech‐like sounds per vocalization and higher pitched vocalizations (including cries)—were associated with greater autism symptom severity. The results suggest that objectively ascertained characteristics of children's vocalizations capture variance in children's restricted and repetitive behaviors that are reflected in clinician severity indices.